Acyclic 1,2-dimagnesioethanes/-ethene derived from magnesium(i) compounds: multipurpose reagents for organometallic synthesis - Dange, D; Gair, A; Jones, D; Juckel, M; Aldridge, S; Jones, C (Royal Society of Chemistry, 2019)
Reactions of three magnesium(i) dimers, [{( Ar Nacnac)Mg-} 2 ] ( Ar Nacnac = [(ArNCMe) 2 CH] − ; Ar = xylyl (Xyl), mesityl (Mes) or 2,6-diethylphenyl (Dep)), with either 1,1-diphenylethylene (DPE), α-methylstyrene (MS), trans-stilbene (TS) or diphenylacetylene (DPA) led to the 1,2-addition of the Mg-Mg bond across the substrate, giving rise to the 1,2-dimagnesioethanes, [{( Xyl Nacnac)Mg} 2 (μ-DPE)], [{( Dep Nacnac)Mg} 2 (μ-MS)], [{( Ar Nacnac)Mg} 2 (μ-TS)] (Ar = Mes or Dep); and a 1,2-dimagnesioethene, [{( Mes Nacnac)Mg} 2 (μ-DPA)]. The reactions involving the 1,1-substituted alkenes are shown to be readily redox reversible, in that the reaction products are in equilibrium with a significant proportion of the starting materials at room temperature. Variable temperature NMR spectroscopy and a van't Hoff analysis point to low kinetic barriers to these weakly exergonic reactions. [{( Mes Nacnac)Mg} 2 (μ-DPE)] and [{( Mes Nacnac)Mg} 2 (μ-DPA)] behave as 1,2-di-Grignard reagents in their reactions with very bulky amido-zinc bromides, yielding the first examples of a 1,2-dizincioethane, [(L*Zn) 2 (μ-DPE)] (L* =-N(Ar*)(SiPr i3 ); Ar* = C 6 H 2 Me{C(H)Ph 2 } 2 -4,2,6), and a 1,2-dizincioethene, [( TBo LZn) 2 (μ-DPA)] ( TBo L =-N(SiMe 3 ){B(DipNCH) 2 }, Dip = 2,6-diisopropylphenyl), respectively. Divergent reactivity is shown for [{( Mes Nacnac)Mg} 2 (μ-DPE)], which behaves as a two-electron reducing agent when treated with amido-cadmium and amido-magnesium halide precursors, yielding the cadmium(i) and magnesium(i) dimers, [ PhBo LCdCd PhBo L] ( PhBo L =-N(SiPh 3 ){B(DipNCH) 2 }) and [L † MgMgL † ] (L † =-N(Ar † )(SiMe 3 ); Ar † = C 6 H 2 Pr i {C(H)Ph 2 } 2 -4,2,6), respectively. A further class of reactivity for [{( Mes Nacnac)Mg} 2 (μ-DPE)] derives from its reaction with the bulky amido-germanium chloride, L*GeCl, which gives a magnesio-germane, presumably via intramolecular C-H activation of a highly reactive magnesiogermylene intermediate, [:Ge(L*){Mg( Mes Nacnac)}]. [{( Mes Nacnac)Mg} 2 (μ-DPE)] can be considered as acting as a two-electron reducing, magnesium transfer reagent in this reaction.